Drafting the Dutch: Selection Biases in Dutch Conscript Records in the Second Half of the Nineteenth Century. Issue 3 (17th June 2020) - Quanjer, Björn; Kok, Jan
ABSTRACT: Conscription records are considered to be the best sources for studying heights over cohorts. This article discusses the various steps and selection mechanisms involved in the conscription system of the Netherlands, which was more or less similar to the systems found in other European countries. Starting with a birth cohort of 4, 436 boys, we run a series of regressions on the likelihood to be registered at all and to have one's height recorded. We discuss the effects of cohort attrition through mortality and migration, and explore familial, social, and religious reasons for evading registration and (medical) examination. We find various kinds of selections, but their effects on the distribution and averages of heights are limited. Thus, heights culled from conscripts records are indeed an excellent indicator of a cohort's biological standard of living. However, researchers focusing on social variation in height need to be aware of the unequal opportunities to evade registration and measurement.